Leveraging Artificial Intelligence (Ai) for the Enhancement of Business Processes Performance - Kánovics, Jakub; Špaček, Miroslav, 1954-; Rejthar, Stanislav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
The master thesis develops and defines a fundamentally improved business process of face-to-face communication analytics with the utilization of AI, ML, and NLP as means of improving the business process performance. To achieve so, from the theoretical point of view, the paper delves into various aspects of artificial intelligence through an extensive literature review. On the other hand, from the practical point of view, the paper analyzes numerous business processes utilizing AI-driven text and call analytics using business process modelling. Additionally, the paper provides practical insights into AI-driven analytics for driving sales and customer experience through a qualitative study consisting of semi-structured interviews and case studies. By the end of the master thesis, readers will have a comprehensive understanding of the AI, ML and NLP technology, and text and call analytics, with the ultimate goal of proposing author’s solution of a fundamentally improved business process of face-to-face communication analytics utilizing AI technology.
Vedoucí práce: Miroslav Špaček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses